2016
DOI: 10.1016/j.ympev.2016.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary history of chloridoid grasses estimated from 122 nuclear loci

Abstract: Chloridoideae (chloridoid grasses) are a subfamily of ca. 1700 species with high diversity in arid habitats. Until now, their evolutionary relationships have primarily been studied with DNA sequences from the chloroplast, a maternally inherited organelle. Next-generation sequencing is able to efficiently recover large numbers of nuclear loci that can then be used to estimate the species phylogeny based upon bi-parentally inherited data. We sought to test our chloroplast-based hypotheses of relationships among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 106 publications
(181 reference statements)
1
23
0
Order By: Relevance
“…Only the portion of the contig matching the references was considered to remove UTRs, potential introns, and other very variable segments. Each sequence retrieved this way was then aligned independently to the reference dataset using Muscle (Edgar 2004), and a phylogenetic tree was inferred using Phyml (Guindon and Gascuel 2003) with a GTR+G+I model, a model that fits the vast majority of genes (e.g., Fisher et al 2016) and is appropriate to infer a large number of trees. Phylogenetic trees were automatically screened, and each contig was assigned to the previously identified gene lineages in which it was nested.…”
Section: Among Photosynthetic Typesmentioning
confidence: 99%
“…Only the portion of the contig matching the references was considered to remove UTRs, potential introns, and other very variable segments. Each sequence retrieved this way was then aligned independently to the reference dataset using Muscle (Edgar 2004), and a phylogenetic tree was inferred using Phyml (Guindon and Gascuel 2003) with a GTR+G+I model, a model that fits the vast majority of genes (e.g., Fisher et al 2016) and is appropriate to infer a large number of trees. Phylogenetic trees were automatically screened, and each contig was assigned to the previously identified gene lineages in which it was nested.…”
Section: Among Photosynthetic Typesmentioning
confidence: 99%
“…[Carex, coalescent based species 3/52 tree, flowering plants, low-copy nuclear genes, low-level phylogenetics, universal hybrid enrichment probes] 40 7/52 Ruane et al 2015), lizards (LeachĂ© et al 2014;Brandley et al 2015;Pyron et al 2016), frogs (Peloso et al 2014) and fishes (Eytan et al 2015) amongst others. In plants, hybrid enrichment 105 probes have been designed for several genera (e.g., de Sousa et al 2014;Weitemier et al 2014;Nicholls et al 2015;Schmickl et al 2015;Stephens et al 2015;Heyduk et al 2016;Johnson et al 2016), a subfamily of palms (Arecoideae, Arecaceae; Comer et al 2016), a subfamily of grasses (Chloridoideae, Poaceae;Fisher et al 2016), and for the sunflower family (Asteraceae; Mandel et al 2015). Although this taxon-specific approach in plants has been successful, it 110 requires new probes to be designed for every group, and the data generated from such studies has limited potential to be reused because the targeted regions are group-specific.…”
Section: /52mentioning
confidence: 99%
“…Genomic targeted enrichment approaches have been shown to be more efficient and economic than Sanger sequencing (Lemmon & Lemmon, 2013; McKain et al, 2018) and have been widely used in phylogenetic studies in recent years (Xi et al, 2014; Fisher et al, 2016; Hart et al, 2016; Mitchell et al, 2017; Couvreur et al, 2018). In this study, we targeted nuclear genes as they have been suggested to hold the greatest potential for investigating the evolutionary history of angiosperms for several reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, nuclear genes have worked well in reconstructing more strongly supported phylogenetic relationships than organellar markers in both deep and shallow time scales (Xi et al, 2014; Mitchell et al, 2017). Secondly, nuclear genes are assumed to be unlinked, decreasing the probability of misleading phylogeny by part of the genes used (Fisher et al, 2016). Lastly, nuclear genes present multiple lineage histories, contrary to plastid genes, which are usually considered to represent a single locus.…”
Section: Introductionmentioning
confidence: 99%